Germany’s Approaches to the Settlement of Contemporary International Conflicts in the post-Soviet Space - N. V. Shevchuk; A. A. Sachik (Евразийская интеграция: экономика, право, политика, 2022)
The article analyzes the mediation activity of Germany in the context of the common European approaches to the peaceful settlement of international conflicts.Aim. To identify the importance of German mediation for foreign policy and its impact on the promotion of peace initiatives in the Eurasian space. Compare the current mediation tactics used by Germany today.Tasks. To analyze the foreign policy instruments of the State in question to promote the peaceful settlement of conflicts in regions of political importance to it, including the post-Soviet space.Methods. The paper uses logical and comparative analysis, a method of working with regulatory legal acts.Results. Mediation serves as an important foreign policy tool of the state in question to promote the peaceful settlement of conflicts in regions of political importance to it, such as the post-Soviet space.Conclusion. The authors show the main approaches of the German Federal Government to crisis prevention, which are based on a broad concept of security. The article provides a categorization of the main instruments of Germany’s participation in mediation processes, namely: participation in formal formats of conflict resolution; participation in informal formats of conflict resolution; confidencebuilding measures. Analyzing the experience of Germany’s participation in peace processes in the postSoviet space, the authors come to the conclusion that the state tries to remain in the shadows, playing the role of a mediator in conflicts, while coordinating its actions with other active actors involved in the region.